AN ANALYSIS OF GRAMMATICAL COHESION IN STUDENTS WRITING RECOUNT TEXT OF GRADE X AT SMA GAJAH MADA MEDAN - Shania Tiopani Pane; Isli Iriani Indiah Br. Pane (Universitas Negeri Medan, 2021)
The aim of this study is to define the different types of grammatical cohesion and to look into the grammatical cohesiveness of students‟ recount text writings based on the use of grammatical cohesive devices. The research was conducted by using descriptive qualitative method that only focuses on on describing data of grammatical cohesive devices that will be found in students‟ recount writings. The data sources are taken from 20 recount texts made by X IS students of SMA Gajah Mada. The data were analyzed used Mayring‟s theory which is consists of data categorization, abstraction, coding the text and result. In this research, the data collected through documentation and worksheet. The finding of this study showed that the grammatical cohesive devices found in the data except ellipsis. Furthermore, it can be concluded that all texts collected are cohesive enough because they all employ grammatical cohesion even though some of the cohesive ties are used incorrectly.Keywords: Cohesion, Recount Text, and Descriptive Qualitative